Social and demographic correlates of male androgen levels in wild white‐faced capuchin monkeys (Cebus capucinus). Issue 7 (7th April 2017) - Schaebs, Franka S.; Perry, Susan E.; Cohen, Don; Mundry, Roger; Deschner, Tobias
Abstract : The Challenge Hypothesis, designed originally to explain the patterning of competitive behavior and androgen levels in seasonally breeding birds, predicts that males will increase their androgen levels in order to become more competitive in reproductive contexts. Here we test predictions derived from the Challenge Hypothesis in white‐faced capuchin monkeys ( Cebus capucinus ), a species that has somewhat seasonal reproduction. We analyzed demographic and hormonal data collected over a 5.25‐year period, from 18 males in nine social groups living in or near Lomas Barbudal Biological Reserve, Costa Rica. Alpha males had higher androgen levels than subordinates. Contrary to our predictions, neither the number of breeding‐age males nor the number of potentially fertile females was obviously associated with androgen levels. Furthermore, male androgen levels were not significantly linked to social stability, as measured by stability of male group membership or recency of change in the alpha male position. Androgen levels changed seasonally, but not in a manner that had an obvious relationship to predictions from the Challenge Hypothesis: levels were generally at their lowest near the beginning of the conception season, but instead of peaking when reproductive opportunities were greatest, they were at their highest near the end of the conception season or shortly thereafter. This lack of correspondence to the timing of conceptions suggests that there may be ecological factors not yet identified that influence ifA levels. We expected that the presence of offspring who were young enough to be vulnerable to infanticide during an alpha male takeover might influence androgen levels, at least in the alpha male, but this variable did not significantly impact results. Abstract : Alpha males had higher androgen levels than subordinates. Social instability and the presence of infants did not affect male androgen levels. The number of males and fertile females co‐residing did not affect male androgen levels.